1995
DOI: 10.1016/0014-5793(95)00538-k
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐induced inactivation of isocitrate lyase in Saccharomyces cerevisiae is mediated by an internal decapeptide sequence

Abstract: In this work we have investigated the role of specific peptide sequences for glucose-inactivation of the yeast isocitrate lyase. Thus, different fragments of the ICLI coding region were fused to the lacZ gene of E. coil to provide a reporter construction. Determinations of/3-galaetosidase activities indicated that the decapeptide sequence KTKRNYSARD, located between amino acid residues 37 and 46 of isocitrate lyase, is important for glucose induced proteolytic inactivation. Further experimental evidence was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Characterisation of this phenomenon has shown that the first step involves reversible inactivation of the enzyme by phosphorylation, while in the second stage final degradation of the protein occurs (Lopez-Boado et al 1988;Ordiz et al 1995). However, preliminary studies of A. nidulans (De Lucas et al 1994b) suggested that proteolysis of the enzyme is the only mechanism involved in the glucose-induced inactivation of isocitrate lyase, although this hypothesis has to be confirmed by additional experiments.…”
Section: Cristina Amor · Ana I Domínguez · J Ramón De Lucas · Fernamentioning
confidence: 88%
“…Characterisation of this phenomenon has shown that the first step involves reversible inactivation of the enzyme by phosphorylation, while in the second stage final degradation of the protein occurs (Lopez-Boado et al 1988;Ordiz et al 1995). However, preliminary studies of A. nidulans (De Lucas et al 1994b) suggested that proteolysis of the enzyme is the only mechanism involved in the glucose-induced inactivation of isocitrate lyase, although this hypothesis has to be confirmed by additional experiments.…”
Section: Cristina Amor · Ana I Domínguez · J Ramón De Lucas · Fernamentioning
confidence: 88%
“…S. cerevisiae FMY402 15 ) (Ordiz et al, 1995), kindly provided by Dr Fernando Moreno (Universidad de Oviedo, Spain), was used in the ICL1 complementation assay.…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%
“…Determination of galactosidase activities of ICL-␤-galactosidase fusion proteins indicated the importance of a decapeptide sequence, located between amino acid residues 37 and 46 of ICL, for glucose-induced degradation of the enzyme (19). This decapeptide is not present in FBPase and other gluconeogenic enzymes.…”
mentioning
confidence: 99%